Multicultural education and the internet : - Gorski, Paul C. (McGraw-Hill, 2001)
This brief, affordable book focuses on the Internet's ability to help facilitate multicultural ideals of inclusive, interactive, and collaborative teaching and learning. The first section covers practical strategies for using the Internet to supplement multicultural teaching practices and will list existing Internet resources with annotations. The second section provides detailed chapter-length lists of Internet resources such as ESL and bilingual sites, subject-specific multicultural sites, lesson plan sites, online journals, and more. Screen shots, site explantations from site creators, and short case essays by teachers who have used the Internet successfully in multicultural teaching practice expand each chapter.